Environmental evaluation of the electric and cogenerative configurations for the energy recovery of the Turin municipal solid waste incineration plant. Issue 7 (July 2014) - Panepinto, Deborah; Genon, Giuseppe
Given the desirability of reducing fossil fuel consumption, together with the increasing production of combustible solid wastes, there is clearly a need for waste treatment systems that achieve both volume reduction and energy recovery. Direct incineration method is one such system. The aim of this work was to analyze the municipal solid waste incineration plant currently under construction in the province of Turin (Piedmont, North Italy), especially the potential for energy recovery, and the consequent environmental effects. We analyzed two kinds of energy recovery: electric energy (electrical configuration) only, and both electric and thermal energy (cogenerative configuration), in this case with a different connection hypothesis to the district heating network. After we had evaluated the potential of the incinerator and considered local demographic, energy and urban planning effects, we assumed different possible connections to the district heating network. We computed the local and global environmental balances based on the characteristics of the flue gas emitted from the stack, taking into consideration the emissions avoided by the substituted sources. The global-scale results provided relevant information on the carbon dioxide emissions parameter. The results on the local scale were used as reference values for the implementation of a Gaussian model (Aermod) that allows evaluation of the actual concentration of the pollutants released into the atmosphere. The main results obtained highlight the high energy efficiency of the combined production of heat and electricity, and the opportunity to minimize the environmental impact by including cogeneration in a district heating scheme.